Polyvinyl Chloride (PVC)-Glycerol with Chitosan Addition for Antibacterial Blood Bag Application - Widiyanti, Prihartini; Tarissa Diandra Putri Wibowo; Baskoro, Andhi; Siswanto (Institute of Topical Disease Universitas Airlangga, 2023)
Blood bag is a medical device that stokes and transports whole blood or blood components. The material that is often used for blood bag membranes is Polyvinyl Chloride (PVC), however the common problem that is bacterial contamination and that material have not antibacterial characteristic. Because of this matter, the aim of this reseach are a blood bag that has antibacterial function is needed and meet the ideal standard as bloodbag. Chitosan as a blood bag membrane material fabrication to get the antibacterial effect. Chitosan is chosen as a blood bag material fabrication to get the antibacterial effect. Chitosan has several specific biocompatibility properties, antibacterial, chelation, and biodegradability. This study used various Chitosan concentrations of 1.5%, 2%, 2.5%, and 3%, and Glycerol was added as a plasticizer. The composition of Chitosan: Glycerol is 1:1. Then, the mixture is added to the PVC solution in a ratio of 1:5 then poured into a petri dish. The results showed characterization that the biocomposite PVC-Glycerol with the addition of 3% concentration of chitosan was the best composition, the tensile strength test result of biocomposite is 21.20 MPa, the absence of membrane pores in the morphology of the blood bag, the hemolytic activity is 0.24%, and the inhibition zones of E. coli and S. aureus, respectively 11.66 mm and 12.66 mm in diameter. Based on the characterization results, the biocomposite PVC-Glycerol membrane with the addition of Chitosan has a very high potential as a candidate for blood bag membranes